Lithuanian Public Police and Police Battalions in 1941–1944 - Bubnys, Arūnas (Genocidas ir rezistencija, 1998)
During the Soviet period, the situation of Lithuanian soldiers during the Nazi occupation could not be studied objectively and in detail. Recently, the operations of the Lithuanian security police battalions have attracted the interest of war crimes’ researchers in the US and Canada, but the motives of the historians working there are not very different from those of the Soviet historians, namely, to find as many war criminals as possible and to exaggerate the involvement of Lithuanians in the Holocaust. This is not to say that there are no dark pages in the history of the Lithuanian police and self–defence units (unjustifiable war crimes), but this aspect was so heavily exploited during the Soviet era that, in the author’s opinion, it has been sufficiently explored and has been exhausted. The aim of this article is to reveal the history of the Lithuanian public police and self–defence units (police battalions) during the Nazi occupation, to present the formation and organisational structure of the Lithuanian police, to describe the chain of command with the German military and civil authorities, to illustrate the mood of the soldiers who served in the police and self–defence units, and to show their attempts to resist the order and demands imposed by the occupiers.
Keywords: German occupation; public police; police battallions; Holocaust